Configuring subsidiary performance in ambidextrous networks: The role of top management team diversity and autonomy. (8th March 2022) - Dahms, Sven; Cabrilo, Sladjana; Kingkaew, Suthikorn
Abstract: Subsidiaries are at the frontline of value creation in modern multinational enterprises. This research is among the first to apply an asset bundling framework to investigate how foreign‐owned subsidiaries achieve higher performance outcomes via ambidextrous network management, that is, with strong exploitative (intraorganizational) as well as strong explorative (interorganizational) network relationships, in emerging markets. Ambidextrous network management may be supplemented by decision‐making autonomy and top management team national diversity. The framework is tested on a sample of subsidiaries located in both Thailand and Singapore. The analysis revealed several configurations that make subsidiaries with ambidextrous networks become successful. Our findings demonstrate to subsidiary managers that exploitation and exploration are complementary for long‐term success in a subsidiary, but that the relative balance between the two is likely to vary according to the nature of subsidiary context‐specific assets.